PENGARUH TERPAAN KONTEN MEDIA SOSIAL INSTAGRAM TERHADAP KARAKTER PRIBADI REMAJA SMAN 5 BATAM: PENDAHULUAN, KAJIAN TEORI, METODOLOGI PENELITIAN, HASIL DAN PEMBAHASAN, SIMPULAN, DAFTAR PUSTAKA - Tampubolon, Hesti Lena Br; Rorong , Michael Jibrael (LPPM Universitas Putera Batam, 2024)
This research was carried out in a high school (SMA) environment with the aim of finding out how teenagers are exposed to Instagram social media content, the uses or interests of teenagers in using Instagram social media and the influence of exposure to Instagram social media content on teenagers' personal character. Instagram is a social media whose active users are teenagers, therefore Instagram social media has a significant personal influence. The research method used in this research is the quantitative method, while the theory used is the S-O-R theory. The population in this study were female students at SMAN 4 Batam with a total of 1,891. Determining the sample in this study used random sampling techniques and the process of determining the number of samples used the Slovin formula so that from this formula a sample of 95 students was produced. Techniques for data analysis use descriptive statistical tests, classical assumption tests, multiple regression and hypothesis tests. The results of the multiple linear regression analysis are Y=20.89 + 0.353, meaning the regression coefficient has a positive value, so it is explained that the direction of the influence of variable X on Y is positive. The results of the coefficient of determination test explain that the influence on the variable exposure to Instagram social media content is 37.6%, while the remaining 62.4% is influenced by variables that are not included in the research that the researchers are currently examining.